PENERAPAN MODEL PROBLEM BASED LEARNING UNTUK MENINGKATKAN HASIL BELAJAR MATEMATIKA SISWA KELAS 2 SD NEGERI UMAN AGUNG - Maryani, Yulia; Binti Khoiriyah; Pixyoriza (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
Yulia Maryani, 2186206001. The Implementation of the Problem Based Learning Model to Improve Mathematics Learning Outcomes of Second Grade Students at SD Negeri Uman Agung. Undergraduate Thesis, Faculty of Teacher Training and Education, Universitas Nahdlatul Ulama Lampung, January 2026. Mathematics learning in the second grade of SD Negeri Uman Agung still shows low learning outcomes. This condition is caused by the learning process that remains teacher-centered, resulting in students experiencing difficulties in understanding the material. Therefore, it is necessary to implement a creative and appropriate learning model, one of which is the Problem Based Learning model. This study aims to improve students’ learning outcomes in mathematics through the implementation of the Problem Based Learning model in the second grade of SD Negeri Uman Agung. This research employed Classroom Action Research (CAR) conducted in two cycles. Each cycle consisted of planning, implementation, observation, and reflection stages. The subjects of this study were 22 second-grade students of SD Negeri Uman Agung. Data were collected through observation, interviews, documentation, and learning achievement tests. The data were analyzed using a mixed-method approach. The results of the study indicate that the implementation of the Problem Based Learning model can improve students’ mathematics learning outcomes. The data from Cycle I showed that 14 students achieved mastery with a percentage of 64%, while 8 students did not achieve mastery with a percentage of 36%. In Cycle II, there was a significant improvement, with 20 students achieving mastery (91%) and only 2 students not achieving mastery (9%). Therefore, the increase from Cycle I to Cycle II was 27%. Based on these results, it can be concluded that the implementation of the Problem Based Learning model was effective in improving students’ mathematics learning outcomes in Grade 2 of SD Negeri Uman Agung.